Developing Inductive Approach-Based Worksheets for Enhancing Students’ Mathematical Generalization Skills - Nirfayanti; Ernawati; Wijaya, Tommy Tanu (Jurnal Riset Pendidikan Matematika, 2025)
In the 21st century, the ability to generalize mathematical concepts is crucial for students' cognitive development. However, teaching materials that fail to support the development of this skill can hinder student learning outcomes. Therefore, educators need effective teaching materials that improve students' ability to generalise. This study aims to develop teaching materials based on an inductive approach to improve students' mathematical generalization skills. This research uses the ADDIE model, which consists of five phases: analysis, design, development, implementation and evaluation. The study used student worksheets that had been validated by subject and media experts. In addition, pre- and post-tests were conducted to assess the effectiveness and practicality of the worksheets. The results indicated that the developed student worksheets met the criteria for validity, practicality, and effectiveness. The validity of the worksheets was confirmed through positive evaluations from two material experts and two media experts. Practicality was determined based on the overall positive feedback from students. Finally, the effectiveness of the worksheets was demonstrated by a significant improvement in students' mathematical generalization skills following the intervention.